SWOT ANALYSIS: REGIONAL GOVERNMENT STRATEGIES IN HANDLING VIOLENCE AGAINST WOMEN - Fatkhana, Sri; Sri Mulya Ningsih, Dwi; Dian Lestari, Aghnia (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
Violence against women in Cirebon City is a phenomenon that needs serious attention. In this research, the author uses SWOT analysis as a relevant framework element to gain an understanding of more efficient strategies to address violence against women. The main objective is to find out the strategies carried out by the Cirebon City regional government in overcoming this problem. Qualitative methods were used in this research, with the aim of comprehensively understanding the behavior, perceptions, motivations, actions, and experiences of research subjects, using descriptive language, and observing subjects in natural contexts. This approach is also supported by various scientific methods. The results of research using SWOT analysis show that the strengths of the Cirebon City Women's Empowerment, Child Protection, Population Control and Family Planning (DP3APPKB) Service are strengthening networks such as developing the Domestic Violence Prevention Task Force (PKDRT), Family Resilience Motivator (Motekar) and other networks to help socialize the Prevention of Violence against Women in the people of Cirebon City. Weaknesses in DP3APPKB Cirebon City, namely the lack of Human Resources such as psychologists and counselors so still rely on outside energy. However, they have opportunities to overcome weaknesses, namely they have P2TP2A for the handling process, which includes legal volunteers and psychologist volunteers. Threats to the Cirebon City DP3APPKB are that there are still many people who do not dare to report and do not complete their reports so that handling is not optimal.